Development and validation of LC-MSMS method for the analysis of amlodipine and perindopril in tablet dosage form - Alaama, Mohamed; Helal Uddin, A.B.M.; Awang, Mohamed; Abbas, Syed Atif (2018)
Introduction: Amlodipine (AMLO) and Perindopril (PER) have been combined in one tablet dosage form which has been proven to be an effective and well tolerated antihypertensive. Many analytical methods were applied for the analysis of AMLO and PER in this combination but most of the methods are time and money consuming. A new sensitive, rapid, and specific LC- MS/MS analytical methods for the analysis of AMLO and PER was developed and validated. Chromatographic conditions for the best results were optimized using design of experiment method. 4 TH PHARMACEUTICAL RESEARCH CONFERENCE 2018 Challenging The Inquisitive Minds: Frontier Of The Future 24 – 26 August 2018 | Cyberjaya, Malaysia